2003
DOI: 10.1038/sj.bjc.6601223
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of tumour apoptosis by human growth hormone via glutathione production and decreased NF-κB activity

Abstract: In addition to its primary role as growth factor, human growth hormone (hGH) can also participate in cell survival, as already documented by its protective effect on human monocytes or human promyelocytic leukaemia U937 cells exposed to a Fas-mediated cell death signal. However, despite similarities in the molecular events following Fas and TNF-a receptor engagement, we report that U937 cells, genetically engineered to constitutively produce hGH, were made more sensitive to TNF-a-induced apoptosis than parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…101 Human growth hormone (GH) can sensitize the AML cell line U937 to TNF or anthracyclin-induced apoptosis via inhibition of NF-kB. 105 Similarly, erythropoietin 106 can sensitize U937 cells to daunorubicin-induced apoptosis. This effect involves an EPO-induced activation of JAK2 and stabilization of IkB.…”
Section: Therapeutic Strategies Targeting Nf-jbmentioning
confidence: 99%
“…101 Human growth hormone (GH) can sensitize the AML cell line U937 to TNF or anthracyclin-induced apoptosis via inhibition of NF-kB. 105 Similarly, erythropoietin 106 can sensitize U937 cells to daunorubicin-induced apoptosis. This effect involves an EPO-induced activation of JAK2 and stabilization of IkB.…”
Section: Therapeutic Strategies Targeting Nf-jbmentioning
confidence: 99%
“…EMSAs NF-kB measurement by EMSAs was performed as reported (Cherbonnier et al, 2003). Renal carcinoma cell lines were cultured for 2 h in the absence or in the presence of 2 mM of VBL alone or in addition to various doses of EPO.…”
Section: Luciferase Reporter Assaysmentioning
confidence: 99%
“…Recently, it has been described that human growth hormone (GH) can sensitize U937 cells to TNF or daunorubicin (Dauno)-induced apoptosis by inhibiting the NF-kB pathway (Cherbonnier et al, 2002;Cherbonnier et al, 2003). Since the receptors for GH and erythropoietin (EPO) share structural features (Bazan, 1990) and both similarly activate the JAK2/ STAT5 pathway (Parganas et al, 1998), we wondered whether EPO might be used as an NF-kB-inhibitory, chemosensitizing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Released NFnB migrates into the nucleus and activates target gene expression (28,29). It has been shown that inhibition of NFnB activation can result in increased sensitivity to anthracyclines (30,31 (34). Our study revealed that the expression of IKBKE was significantly associated with daunorubicin cytotoxicity.…”
Section: Discussionmentioning
confidence: 51%